Proteinase-activated receptors 1 and 2 regulate invasive behavior of human melanoma cells via activation of protein kinase D1 - Kempkes, Cordula; Stróżyk, Elwira; Schneider, Stefan W. (The journal of investigative dermatology, 2012)
Recent studies have indicated an important role of proteinases and proteinase-activated receptors (PARs) in tumorigenesis. Although a role for PARs has been described in various skin tumors including melanoma, the underlying cellular mechanisms have not been understood. Recent studies have suggested PAR1 as a regulator of melanoma cell growth and metastasis by affecting angiogenic and invasive factors. Moreover, changes in the expression patterns of PAR1 and PAR2 correlate with skin cancer progression, and PAR1 is overexpressed in melanoma. Therefore, we sought to elucidate the putative role of PAR1- and PAR2-mediated signal transduction pathways during melanoma progression. Activation of both PAR1 and PAR2 led to rapid phosphorylation of protein kinase D1 (PKD1) in cultured WM9 melanoma cells. PKD1 is known to be involved in cell migration, integrin regulation, and intracellular vesicle transport. Downregulation of PKD1 by siRNA resulted in diminished proliferation, decreased αvβ3 integrin regulation, and secretion of pro-angiogenic chemokine IL-8 in WM9 cells. In conclusion, our results show that PAR1 and PAR2 are involved in WM9 cell proliferation and secretion of IL-8 by activation of PKD1. Inactivation of the PKD1 pathway may be beneficial for the inhibition of PAR-induced melanoma proliferation and for maintenance of the inflammatory tumor environment.